THE SCIENTIFIC RELATIONSHIP BETWEEN THE PROCESS OF KNOWLEDGE MANAGEMENT COMPONENTS AND THE EFFECTIVENESS OF INDICATORS OF COMMUNICATION SKILLS OF THE MINISTRY OF SPORTS AND YOUTH: WITH THE AIM OF INVESTIGATING THE ROLE OF APPLYING AND USING INFORMATION AN - Ali Asghar Rashid,; Vahid Bakhshalipour, (Sport Scientific And Practical Aspects, 2025)
Aim and Background: The use of information and communication technology can lead to the development of requiredskills in sports employees, and the present research aims to approach the relationship between the process of knowledge management components and the effectiveness of indicators of communication skills of employees of the Ministry of Sports and Youth. The role of applying and using information and communication technology skills was investigated. Method: The research is a descriptive research and the research method is correlational and practical in terms of purpose. The statistical population of this research is made up of all the employees of sports and youth departments, which according to the statistics in 2022, were 280 people. To analyze the data, K-S, Kruskal-Wallis, Yeoman-Whitney, Spearman correlation and regression tests were used. Results: 52.85% had graduate and undergraduate degrees, 38.85% had master's degrees, and 1.72% were doctoral and doctoral students. The correlation coefficient between ICT and knowledge management components is 0.369 and ICT with communication skills indicators is 0.361. Conclusion: The results of statistical data showed that the level of access and use of information and communication technology in men is higher than women, but the level of communication skills in girls is higher than boys. Therefore, it is suggested that the country's employees in general and physical training organizations in particular pay special attention to information literacy and communication skills.